Graphene-like holey Co3O4 nanosheets as a highly efficient catalyst for oxygen evolution reaction. (December 2016) - Dou, Yuhai; Liao, Ting; Ma, Zongqing; Tian, Dongliang; Liu, Qiannan; Xiao, Feng; Sun, Ziqi; Ho Kim, Jung; Xue Dou, Shi
Abstract: Co3 O4 nanosheets with a graphene-like holey structure are successfully synthesized through a bottom-up self-assembly approach and utilized as a catalyst for the oxygen evolution reaction (OER). This unique nanostructure possesses a large fraction of low-coordinated surface atoms and highly accessible surface areas due to its atomic thickness and mesoporosity, which could provide abundant active sites and facilitate the electrode/electrolyte contact for OER catalysis. In addition, density functional theory (DFT) calculations reveal that the loss of the neighboring layers gives the ultrathin nanostructure remarkable lattice distortion, which leads to decreased energy barriers for facile mass conversion and transfer on the surface of the catalyst. As a result, the graphene-like holey Co3 O4 nanosheets exhibit excellent OER catalytic performance with low onset potential of 0.617 V vs. Hg/HgO, high current density of 12.26 mA cm -2 at 0.8 V vs. Hg/HgO, and long-term stability with negligible fading in current density after 2000 cycles, significantly outperforming the performances of conventional Co3 O4 nanostructures and commercial IrO2 . This unique graphene-like holey structure should be of great benefit for applications ranging from electronic devices to energy conversion and storage systems. Graphical abstract: Highlights: Graphene-like holey Co3 O4 nanosheets are prepared via a bottom-up self-assembly approach. The atomic thickness and mesoporosity provide numerous low-coordinated surface atoms. The lattice structural distortion leads to the redistribution of surface electron density. The Co3 O4 nanosheets exhibit high catalytic activity towards oxygen evolution reaction.